(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
Bhagandara is a chronic purulent inflammation usually affects perianal region, anal canal and rectum. It initially manifested by an abscess followed by continuous discharge of pus through the tract and leads to an unhealed condition. Improper care and negligence to the disease lead the patient to seriousness occasionally. Now-a-days, management of Bhagandara with Ksharasutra is gained popularity for its minimal invasive and complete cure of the disease but corrosiveness and pain during application of Ksharasutra still remain as a drawback to the approach. This study includes preparation of three types of Ksharasutra and comparative effect of Ksharasutra in the management of Bhagandara. Considering the above problem a thorough review was done in order to find out any solution to solve the purpose of Ksharasutra without pain. Further, it is also revealed that the corrosive agent usually in the preparation of ksharasutra is Snuhi ksheera (Euphorbia nerifolia). The relevant study proved that ksharasutra can also be prepared with Guggulu (Comiphora mukulu) and Udumbara latex (Ficus glomerata) instead of Snuhi ksheera. Thus evaluation of the effect of such Ksharasutra is not methodically done yet. In order to evaluate the effects of ksharasutra prepared out of Guggulu and Udumbara latex is selected for the purpose of the study.